2010
DOI: 10.2514/1.46530
|View full text |Cite
|
Sign up to set email alerts
|

Computational Investigation of Microscale Coaxial-Rotor Aerodynamics in Hover

Abstract: In this work, a compressible Reynolds-Averaged Navier Stokes (RANS) solver is extended to investigate the aerodynamics of a micro-scale coaxial rotor configuration in hover. This required the following modifications to the solver: implementation of a time-accurate low Mach preconditioner, implementation of a sliding mesh interface boundary condition, improvements in the grid connectivity and parallelization of the code.First, an extensive validation study on the prediction capability of the solver is performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…Overall, it is shown that NVLM predicts thrust within 6% of experimental values. This level of accuracy is in line with previous works on low Reynolds number rotors [14][15][16]. Note that results obtained from NVLM depend on aerodynamic polars used as input for the look-up table procedure.…”
Section: Comparison Against Experimentssupporting
confidence: 88%
“…Overall, it is shown that NVLM predicts thrust within 6% of experimental values. This level of accuracy is in line with previous works on low Reynolds number rotors [14][15][16]. Note that results obtained from NVLM depend on aerodynamic polars used as input for the look-up table procedure.…”
Section: Comparison Against Experimentssupporting
confidence: 88%
“…In this arrangement, the body-fitted blade meshes are embedded inside a Cartesian off-body mesh to capture the entire wingwake aerodynamics. The solver uses a novel Implicit Hole-Cutting (IHC) technique [17], which has been efficiently used in several computational studies on complex rotary wing flows [18,19,13,14] B. Low-fidelity Model: Vortex Panel Method The low-fidelity model uses vortex panels [20] to analyze forces exerted on a lifting surface. The lifting surface is partitioned into vortex panels (of strength Γ i ) in the stream-and span-wise directions and bound vortices are placed at the quarter-chord location of each panel.…”
Section: Methodsmentioning
confidence: 99%
“…Deng et al [8] analyzed the aerodynamic characteristics of coaxial rotors at a high-speed both in hover and forward flight with the wind tunnel test and numerical method. Lakshminarayan et al [9] obtained the flow field distribution characteristics of coaxial rotors in hover with the computational fluid dynamic (CFD) method. Tan et al [10] proposed an unsteady aerodynamic analysis to analyze the aerodynamic interference between coaxial rotors with a vortex particle method.…”
Section: Introductionmentioning
confidence: 99%